Toward independent L2 readers: Effects of text adjuncts, subject knowledge, L1 reading, and L2 proficiency - Brantmeier, Cindy; JoAnn Hammadou Sullivan; Strube, Michael (Reading in a foreign language, 2014)
With 97 learners in an advanced Spanish course, the study examines the effects of textual enhancement adjuncts, prior subject knowledge, first language (L1) reading ability, and second language (L2) Spanish proficiency on L2 comprehension of scientific passages. Readings included two texts with two types of embedded questions: a pause or written answer. MANOVA was used to examine the main effects and interaction of textual enhancement adjuncts on three types of comprehension tasks. Findings revealed that embedded questions did not assist L2 readers to comprehend better. The effect of embedded questions on comprehension was not moderated by L1 reading ability, L2 overall proficiency nor by prior subject knowledge. Although prior subject knowledge and L1 reading comprehension were positively related to comprehension, the use of textual enhancements did not compensate for weaknesses. This study provided evidence that, with advanced L2 learners, embedded questions do not aid L2 reading comprehension.